Identification of Style and Characteristics of Colonial Buildings of URC City Post in Lhokseumawe City - Febri Tika Sari; Armelia Dafrina; Dela Andriani; Fidyati Fidyati; Muthmainah Muthmainah; Mochamad Ari Saptari; Diana Khairani Sofyan (Electronic Journal of Education, Social Economics and Technology, 2025)
The URC City Police Post building in Lhokseumawe City is a legacy of Dutch Colonial Architecture, showcasing a blend of European style (Dutch Land) and local Indonesian elements, known as the Indische Empire Style. This building has a distinctive visual character and is monumental. Some of the main characteristics of colonial architecture found in this building include the presence of sturdy materials such as specially blended cement, terrazzo for floors, Geveltoppen, acroterie roofs, a geometric symmetrical facade, the use of wooden-framed windows, and dormer elements. Classical European decoration (pillars, capitula) is combined with local decorative variations, such as on the cripedoma (entrance decoration) or tympanon. This study aims to identify and analyze the style and characteristics of colonial architecture found in the URC City Police Post building, located in Banda Sakti District, Lhokseumawe City. The research method used is descriptive with a qualitative approach through field surveys, photographic documentation of the object, and direct observation of building elements.